An initial assessment of the value of Allam Cycle power plants with liquid oxygen storage in future GB electricity system. (August 2019) - Mitchell, Charlotte; Avagyan, Vitali; Chalmers, Hannah; Lucquiaud, Mathieu
Highlights: Allam Cycle process model with bypass stream heat source achieves 58.0% net efficiency. Novel operational modes presented to enhance operational flexibility by using O2 storage to decouple O2 production from CO2 capture. Case study of future GB electricity system with conventional and flexible Allam Cycles in bespoke Unit Commitment model. Allam Cycle plants tend to operate as baseload due to competitive efficiency and minimal CO2 emissions. Abstract: The Allam Cycle is a novel oxy-combustion gas turbine power cycle with a reported net cycle efficiency of 58–60% LHV and near-zero operating emissions. An Allam Cycle process model is developed displaying a net cycle thermal efficiency (LHV) of 58.0%, a higher value than previously reported in the literature, due to the inclusion of a bypass stream heat source. Novel modes of operation are added to improve plant operational flexibility, including a temporary increase in cycle efficiency to 66.1%, with the use of liquid oxygen storage to shift the energy penalty of oxygen production. This facilitates decoupling oxygen and electricity production and operates as a form of energy storage. For the first time, a purpose-built Unit Commitment and Economic Dispatch (UCED) model is used to investigate the impact of Allam Cycle plants and of liquid oxygen storage on system costs and grid CO2 intensities, taking the illustrative case of the GB electricity system. Over a representative winter week with high net demand, a fleet of 5–15 Allam Cycle plants operates with a capacity factor of, respectively 97%-90%, reducing system costs by 2.6%–6.7% and reducing electricity grid average CO2 intensity by 7.9%–19.0%. Adding oxygen storage to these plants allows surplus renewable energy generation to be stored, thus avoiding wind curtailment. Our initial findings indicate that oxygen storage can be valuable to both to plant operators and the system operators, but also that further work is required to evaluate non-energy revenue streams from the ancillary service market to determine whether the capital expenditure of liquid oxygen storage could be justified without financial incentives.